KOMITMEN GURU DALAM MELAKSANAKAN TUGAS DI SEKOLAH MENENGAH ATAS (SMSA) KECAMATAN ROKAN IV KOTO - Wirdatul Jannah (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information about the Teachers Commitment To Carry Out The Task. The population is 54 teachers and the sample is 54 The instrument of this research is question with Likert scale models that had tested for validity and realibility. Data analyzed using mean score and performance level. The result of this research are the Teachers Commitment To Carry Out The Task In SMANegeri Kecamatan Rokan IV Koto Kabupaten Rokan Hulu stay in good category. Key word : Teachers Commitment